+0  
 
0
126
1
avatar+50 

Using the functions below to produce new functions based upon the description and identify the domain and range of the new functions.

 

f(x)=3x+3

h(x)=e^(2x+1)

i(x)=x^2+4x+3

 

 

    

      1.   r(x)=h(i(x))

 

    

      2.   t(x)=f((h(i(x)))

Bobbly  Jun 7, 2018
 #1
avatar+92344 
+2

f(x)=3x+3

h(x)=e^(2x+1)

i(x)=x^2+4x+3

 

1.   r(x)=h(i(x)).....here. we are putting the function "i"  into the function "h"  

 

r(x)  = e^[(2 (x^2 + 4x + 3) + 1]

r(x)  = e^[2x^2 + 8x + 6 + 1]

r(x)  = e^[2x^2 + 8x + 7]

 

    

 2.   t(x)=f((h(i(x))).......here we are putting the first result into  "f"

 

t(x) = 3(e^[2x^2 + 8x + 7 ] ) + 3  =

t(x) = 3 [ e^(2x^2 + 8x + 7)  + 1 ]

 

 

 

cool cool cool

CPhill  Jun 7, 2018

23 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.